Trading Analysis Of The Kopay Chili - Kinanti Azani, Fauzia; Hakimi, Rini; Hidayat, Rian (JURNAL AGRIBISAINS, 2024)
Chili is one of the horticultural crops with the most market demand. One of the local varieties that originated from Payakumbuh is Kopay chili. The trading process of the product can influence the fluctuating price. The trading channel is efficient if the system uses the minimum possible cost to distribute the product to consumers. This study aims to describe the trading channels and functions and analyze the trading margins and efficiency of the Kopay chili in Kelurahan Koto Panjang Dalam. This study used a survey method with deep interviews and questionnaires. The number of samples interviewed was 16 farmers, 7 retailers and 10 consumers. The analysis used is descriptive qualitative and quantitative. The result showed two trading channels: channel one (farmers – final consumers) and channel two (farmers – retailers – final consumers). The functions of the trading system are exchange function (purchase and sale), physical function (storage and transportation),and support function (standardization and risk management). The trading margin of channel one is IDR 8.500/kg, while channel one does not have a trading margin because farmers sell the chili directly to consumers. Both trading channels of Kopay chili in Kelurahan Koto Panjang Dalam are efficient, with an efficiency level of 0.37% and 4.19%, respectively.